Perancangan Sistem Electronic Voting untuk Pemilihan Ketua OSIS di SMAN 25 Garut - Topan Setiawan (Jurnal Accounting Information System (AIMS), 2021)
The development of increasingly modern technology has been widely used by humans in all aspects, be it education, defense, health, psychology, communication and so on. This is inseparable from the role of technology which makes human work easier, faster and more accurate. The election of the student council president is one of the activities that must be carried out by SMAN 25 Garut every year. Currently the method of selecting the student council president is carried out using conventional techniques, namely voting by punching ballots, then calculating the results of the recapitulation manually. This technique is in fact ineffective and inefficient because it requires a lot of resources. To answer these problems, an electronic voting (e-voting) system is proposed. E-voting is seen as being able to answer these problems because it can facilitate and speed up the voting process and vote counting so that the spent resources can be minimized. The e-voting system was built using the system development life cycle (SDLC). Which consists of identification, analysis, design, construction, testing, implementation. The testing phase was carried out by observing, interviewing, and studying literature. The results of the analysis were then analyzed, then designed using UML modeling. Meanwhile, the application program is designed using the CodeIgniter framework, the PHP programming language and the MySQL database. Based on the results of research and testing, it is concluded that the e-voting system is more effective in terms of implementation, and more efficient in terms of costs, personnel and implementing personnel.